Archaeological survey and understanding the rural landscape in Byzantine Greece: some specific examples - Gregory, Timothy E.; Tzortzopoulou-Gregory, Lita (Journal of Greek Archaeology, 2020)
In a review of the second volume of the Nemea Valley Archaeological Project Series, a significant contribution in the use of archaeological survey data to explore complex sociopolitical phenomena in the development of the medieval settlement pattern of the northeastern Peloponnese, Michael Given states the following: ‘This volume publishes valuable and interesting material on a period for which, even after some four decades of intensive archaeological survey, there is a striking lack of fully published survey results. This in itself is a major contribution, particularly when combined with the high quality of the original survey, the care with which the pottery and site descriptions are presented, the extensive historical background and the superb illustrations. The volume itself does not present a fully integrated archaeological, historical, and landscape analysis of this important material. Its real value, however, is that it allows us all to do our own integration and analysis.’ Our paper seeks to follow on from this final statement, and as such it wishes first to investigate some general considerations about survey archaeology in the broader world of the eastern Mediterranean, and to then examine more specifically the ways in which they are appropriate to the medieval period in ongoing research. Drawing from our own survey work in northern Kythera and the eastern Korinthia, we will attempt to demonstrate the limitations of an overarching diachronic approach to archaeological survey, and the need for continuous re-evaluation of a survey’s research design and methodology to the specific demands dictated by each different archaeological/historical period.